Pelaksanaan Perjanjian Kerja Waktu Tertentu di Lim Siang Huat Group - Winsherly Tan; Akbar Putra Jako (Fakultas Hukum, Universitas Internasional Batam, 2018)
Work agreements has substantial benefits to the parties. This should be realized because a work agreement created and adhered to properly will be able to create a job of peace and guarantee the certainty of rights and obligations for both workers and employers. The problem in this research is that there are still violations committed by the entrepreneur, Lim Siang Huat Group to the workers regarding the provision of certain time work agreement that is not in accordance with Act Number 13 Year 2003 on Manpower. The type of research used by the author is empirical law research, then the type of data used is Primary Data as the main data and Secondary Data as supporting data. Primary data used by the author in the form of observation and interviews at the Disnaker Batam Office, and of course Lim Siang Huat Group which is the focus on this research. Based on the results of this study it can be concluded that there are still violations committed by the entrepreneur, Lim Siang Huat Group against workers regarding the provisions of work agreement for a specified time not in accordance with Article 59 of Act Number 13 Year 2003 on Manpower. Based on that article, if there is any violation, a work agreement for a specified time by law shall be changed into a work agreement for an unspecified time.